Type specimens of Colletes Latreille (Hymenoptera, Colletidae) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg, with description of a new species - Proshchalykin, Maxim Yu.; Kuhlmann, Michael (Zootaxa, 2015)
The type specimens of Colletes Latreille 1802 deposited in the Zoological Institute, Russian Academy of Sciences (St. Petersburg) are reviewed. Precise information about types of 30 taxa are provided (12 described by J. Noskiewicz; 9 by F. Morawitz; 8 by M. Kuhlmann and M. Proshchalykin; 1 by H. Friese). Lectotypes are designated here and illustrated for the following six nominal taxa: Colletes alpinus Morawitz 1872, C. caspicus Morawitz 1874, C. montana Morawitz 1876, C. squamosus Morawitz 1877, C. tuberculatus Morawitz 1893, and C. wollmanni Noskiewicz 1936. Colletes alpinus was synonymized with C. impunctatus Nylander 1852 but is now recognized as a synonym of C. floralis Eversmann 1852. Colletes morawitzensis Kuhlmann & Proshchalykin, sp. nov. is described based on a male specimen from Turkmenistan and deposited in the Morawitz collection.